Interaction of angiotensin receptor type 1 blockers with ATP-binding cassette transporters - Weiß, Johanna; Sauer, Alexandra; Divac, Nevena; Herzog, Melanie; Schwedhelm, Edzard; Böger, Rainer H.; Haefeli, Walter E.; Benndorf, Ralf (Biopharmaceutics & drug disposition, 2010)
ATP-binding cassette (ABC)-transporters, such as P-glycoprotein (P-gp/ABCB1), multidrug resistance-associated proteins (MRPs/ABCCs) and breast cancer resistance protein (BCRP/ABCG2) transport numerous drugs thus regulating their absorption, distribution and excretion. Angiotensin receptor type 1 blockers (ARBs), used to treat hypertension and heart failure, are commonly administered in combination therapy. However, their interaction potential is not well studied and their effect on ABC-transporters remains elusive. The study therefore aimed to elucidate the effect of various ARBs (telmisartan, candesartan, candesartan-cilexetil, irbesartan, losartan, olmesartan, olmesartan-medoxomil, eprosartan) on ABC-transporter activity in vitro...
Gesehen am 19.10.2023